Charting African Prosperity Gospel economies - Heuser, Andreas (HTS teologiese studies, 2016)
This article maps the vital debate on Prosperity Gospel in Africa and its relevance for socioeconomic change. Prosperity Gospel centres mainly on speech acts surrounding faith, wealth and victory, combined with ritual enactments around secondary evidences of divine blessings. Claiming this-worldly success and material well-being as signs of grace it has captured public spheres and has created African religio-scapes of prosperity. The survey on the socioeconomics of African prosperity-oriented Pentecostalism firstly traces the historic genealogy of Prosperity Gospel as transposable message. It appears as a generic formula in paradigmatic reinventions of Pentecostalism in post-second and/or cold war America and in its globalisation in postcolonial Africa. The double resignification of Pentecostal theology - a rereading of ‘mammon’ alongside a new ethic of being in the world - relates to the question of socioeconomic agency. Academic discourse connects Prosperity Gospel social capital with interpretations of its ritual texture thriving around rituals of tithings and offerings. Prosperity Gospel economies are profiled as forms of sacral consumption or sacrificial economy, or else as Pentecostal kleptocracy. Contrarily Prosperity Gospel is portrayed as a variant and porter of African social change. The contextualisation of Prosperity Gospel highlights diverse social agency in different milieus. Rural and peri-urban theologies of survival differ from urban progressive and metropolitan business management Prosperity Gospel. The findings defy generalised views on Prosperity Gospel socioeconomics. African Prosperity Gospel indicates a transformative potential in immediate social relationships, whereas claims of impacting structural parameters of society remain, with a few exceptions, part of Pentecostal imagination.